The Influence of Intellectual Capital on Corporate Financial Performance (An Empirical Study of Technology Sector Companies Listed on the IDX for the 2022-2025 Period) - Hafiyan Akbar Royyan; Rediyanto Putra (Takaza Innovatix Labs Ltd., 2026)
This study examines the effect of Intellectual Capital, as measured by the Value Added Intellectual Coefficient (VAIC), on financial performance, proxied by Return on Assets (ROA), in technology sector companies listed on the Indonesia Stock Exchange for the 2022–2025 period. This study uses a quantitative approach with secondary data obtained from audited annual financial reports. The study population was technology sector companies, with a final sample of 23 companies or 92 observations selected using a purposive sampling technique. Data analysis was performed using SPSS through descriptive statistical tests, classical assumption tests, and multiple linear regression with Firm Size and Debt to Asset Ratio (DAR) as control variables. The results show that Intellectual Capital has no significant effect on financial performance (ROA). However, the addition of control variables improves the model's ability to explain variations in financial performance, although the main effect remains insignificant. This suggests that the financial performance of technology companies is more influenced by financial and structural factors than intellectual capital efficiency. The study concludes that Intellectual Capital is not a direct determinant of short-term financial performance in technology companies in Indonesia. Further research is recommended to expand the measurement methods, extend the research period, and expand the research objects.